Partial Facetectomy for Lumbar Foraminal Stenosis - Kevin Kang; Juan Carlos Rodriguez-Olaverri; Frank Schwab; Jenifer Hashem; Afshin Razi; Jean Pierre Farcy (Advances in Orthopedics)
Background. Several different techniques exist to address the pain and disability caused by isolated nerve root impingement. Failure to adequately decompress the lumbar foramen may lead to failed back surgery syndrome. However, aggressive treatment often causes spinal instability or may require fusion for satisfactory results. We describe a novel technique for decompression of the lumbar nerve root and demonstrate its effectiveness in relief of radicular symptoms. Methods. Partial facetectomy was performed by removal of the medial portion of the superior facet in patients with lumbar foraminal stenosis. 47 patients underwent the procedure from 2001 to 2010. Those who demonstrated neurogenic claudication without spinal instability or central canal stenosis and failed conservative management were eligible for the procedure. Functional level was recorded for each patient. These patients were followed for an average of 3.9 years to evaluate outcomes. Results. 27 of 47 patients (57%) reported no back pain and no functional limitations. Eight of 47 patients (17%) reported moderate pain, but had no limitations. Six of 47 patients (13%) continued to experience degenerative symptoms. Five of 47 patients (11%) required additional surgery. Conclusions. Partial facetectomy is an effective means to decompress the lumbar nerve root foramen without causing spinal instability.